2006
DOI: 10.1111/j.1365-2796.2006.01728.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of renal dysfunction in patients with stable angina pectoris

Abstract: Objective. Impaired renal function is emerging as an independent risk factor for cardiovascular (CV) disease. We analysed the prognostic implications of estimated renal function in patients with angina pectoris. Design. Post hoc analysis of the Angina Prognosis Study In Stockholm (APSIS). The estimated creatinine clearance (eCrCl) was calculated according to the Cockcroft-Gault formula in 808 patients. Outcomes were compared for subgroups with CrCl ‡90, 60-89 and<60 mL min )1 . Setting. Hospital-based study wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
4
1
Order By: Relevance
“…Furthermore, in the current study, risk prediction by serum creatinine was superior to estimated creatinine clearance. We have previously shown that estimated creatinine clearance provides risk prediction, particularly among men [5]. However, in the present multivariate analyses, serum creatinine was a simple and useful marker for CV risk in stable angina pectoris.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Furthermore, in the current study, risk prediction by serum creatinine was superior to estimated creatinine clearance. We have previously shown that estimated creatinine clearance provides risk prediction, particularly among men [5]. However, in the present multivariate analyses, serum creatinine was a simple and useful marker for CV risk in stable angina pectoris.…”
Section: Discussioncontrasting
confidence: 49%
“…ST depression during LTER < 0Á05 < 0Á05 [11] ST depression > 30 min during LTER < 0Á05 [11] Echocardiography LVEDD < 0Á001 [12] LVESD < 0Á001 [12] were considered normal, and by creatinine clearance, calculated according to the Cockroft-Gault formula [5]. Specially trained research nurses performed an interview regarding psychosocial factors based on standardised questionnaires for the evaluation of psychosomatic symptoms, job strain, self-rated Type A behaviour including hostility, sleep disturbances and self-rated overall life satisfaction.…”
Section: Initially Studied Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies, although limited in follow-up, reported consistent findings in patients with non-ST elevation MI and stable angina. 5,19 Whereas CKD has been found to be a risk factor for increased all-cause mortality up to 10 yr in the general population, 20 -24 to our knowledge, no previous study addressed long-term mortality specifically in patients who were hospitalized with AMI. We further add to the literature an analysis of the relative importance of renal function compared with traditional risk factors.…”
Section: Previous Studiesmentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Despite growing appreciation for the importance of CKD in patients with acute myocardial infarction (AMI), no previous study has investigated longterm mortality risks associated with the entire spectrum of renal function. Furthermore, it is unclear whether the magnitude of mortality risks in patients with impaired function changes over time.…”
mentioning
confidence: 99%